Suppression of mammary epithelial cell differentiation by the helix-loop-helix protein Id-1. - Desprez, P Y (1995)
Cell proliferation and differentiation are precisely coordinated during the development and maturation of the mammary gland, and this balance invariably is disrupted during carcinogenesis. Little is known about the cell-specific transcription factors that regulate these processes in the mammary gland. The mouse mammary epithelial cell line SCp2 grows well under standard culture conditions but arrests growth, forms alveolus-like structures, and expresses beta-casein, a differentiation marker, 4 to 5 days after exposure to basement membrane and lactogenic hormones (differentiation signals). We show that this differentiation entails a marked decline in the expression of Id-1, a helix-loop-helix (HLH) protein that inactivates basic HLH transcription factors in other cell types. SCp2 cells stably transfected with an Id-1 expression vector grew more rapidly than control cells under standard conditions, but in response to differentiation signals, they arrested growth and formed three-dimensional structures similar to those of control cells. Id-1-expressing cells did not, however, express beta-casein. Moreover, 8 to 10 days after receiving differentiation signals, they lost three-dimensional organization, invaded the basement membrane, and then resumed growth. SCp2 cells expressing an Id-1 antisense vector grew more slowly than controls; in response to differentiation signals, they remained stably growth arrested and fully differentiated, as did control cells. We suggest that Id-1 renders cells refractory to differentiation signals and receptive to growth signals by inactivating one or more basic HLH proteins that coordinate growth and differentiation in the mammary epithelium.